ANALISIS NILAI SOSIAL DALAM CERITA PENDEK PILIHAN KOMPAS 2019 SERTA KELAYAKANNYA SEBAGAI ALTERNATIF BAHAN AJAR SASTRA DI SMP - Ardi Nugroho; U'um Qomariyah (Universitas Muhammadiyah Surakarta, 2022)
Teaching social values in school can possibly be applied in Indonesian language learning usingliterary works, including short stories. Students will be able to gain experiences in terms ofappreciation to particular phenomena in the environment. As the result, they can apply socialvalues obtained from the short stories in daily life. This research aims (1) to analyze the socialvalues contained in the 2019 Selected Short Stories by Kompas; and (2) to investigate itsfeasibility as an alternative learning material for literature studies. This research usesqualitative descriptive methods with a sociological approach to literature. Based on the results,there are various social values found in the 2019 Selected Short Stories by Kompas, such astolerance, dedication, mutual help, kinship, unselfishness, affection, discipline, empathy, justice,teamwork, and democracy. Furthermore, regarding the feasibility of 2019 Selected Short Storiesby Kompas as a learning material for literature studies, it was found through three criteria,including aspect of language, aspect of psychology, and aspect of background culture. Accordingto those three criteria, nine short stories are considered worthwhile to be used as an alternativelearning material for literature studies in junior high school.Keywords: material for literature, short stories, social value